Dinamika Umat Kristen Masehi Advent Hari Ketujuh: Studi Kasus di Kudus Jawa Tengah - Moh Rosyid (Prodi Sosiologi Agama FIS Universitas Islam Negeri Sumatera Utara, 2020)
The purpose of writing this text is presenting to give readers an understanding that Kudus is a plural city. There are Muslims, Catholics, Hindus, Buddhists, Confucians, Christians with various denominations, Adventist Christian congregations and also people of indigenous religions. This manuscript data was obtained through interview, discussion, and observation with a qualitative descriptive approach. The initial embryo of the Adventist congregation in Kudus due to the removal of workers in Kudus, they joined their worship in Pati, a neighboring city. In the course of time, there were other Adventists in Kudus so the congregation was held at a house in Kudus and served by Adventist pastors. There is strong family ties supporting the church even though the number does not increase significantly. During the New Order era, they were rejected by Islamic organizations when they were about to establish a church. With the patience of the congregation, the congregation and other Adventist religious activities are now centralized in a housing complex in Kudus in the house of the priest and his families.